Methylene Blue Dye Photodegradation during Synthesis and Characterization of WO3 Nanoparticles. (22nd July 2022) - Surakasi, Raviteja; Alimuddin,; Rao, Yenda Srinivasa; Sanuj, Ashitha K.; Patil, Pravin P.; Jayaganthan, A.; Hechhu, Ramana
Abstract : Semiconductor-based photocatalytic systems have found widespread use in environmental pollution cleanup and renewable energy production. In this study, we synthesized WO3 as a catalyst for the degradation of methylene blue, a thiazine dye, which was used in the previous work. The hydrothermal process is used to create WO3 nanoparticles, which are made from sodium tungstate. When it comes to confirming the nanoparticles, many characterization techniques are employed, including X-ray diffraction (XRD), Fourier transform infrared (FTIR), UV-Vis diffuse reflectance spectrometer (DRS), X-ray photoelectron spectroscopy (XPS), and field emission–scanning electron microscope (FE-SEM). The existence of monoclinic crystalline structure is shown by XRD, with the average crystalline size being around 34 nm. FTIR confirms the presence of metal oxides. The pellucid absorption extremity in the UV-Vis region corresponds to the rudimentary absorption of the WO3 semiconductor. FE-SEM confirms square-shaped nanoplates with EDX address the occurrence of elemental tungsten. The photocatalytic activity of WO3 nanoparticles against methylene blue is taken for at different intervals of time that confirms MB's degradation. Our present work suggests that prepared nanoparticles should be potential for photocatalysts using various industrial dyes.